2011
DOI: 10.1177/0273475310389153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nonverbal Signals on Student Role-Play Evaluations

Abstract: Although salespeople have long been urged to recognize and adapt to customer needs and wants by observing communications style and other cues or signals by the buyer, nonverbal communications by the salesperson have received much less empirical scrutiny. However, nonverbal communications may be important in this context; research in several disciplines intimates that nonverbal signals are equally, perhaps more, important than verbal signals in persuasive communications. In a first study, the authors examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Of particular interest was experiential learning, which was significant in impacting self-efficacy only when role-plays and participation in sales fraternities were excluded. Role-plays are a staple of most sales programs (Inks & Avila, 2008; Moncrief, 1991; Moncrief & Shipp, 1994; Sojka & Fish, 2008; Taute et al, 2011; Widmier et al, 2007), and, as expected, were reported as being used in almost all (92%) of respondents’ sales classes at one time or another. However, it appears that role-plays must be supplemented with “working life” experiential exercises to be most effective.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Of particular interest was experiential learning, which was significant in impacting self-efficacy only when role-plays and participation in sales fraternities were excluded. Role-plays are a staple of most sales programs (Inks & Avila, 2008; Moncrief, 1991; Moncrief & Shipp, 1994; Sojka & Fish, 2008; Taute et al, 2011; Widmier et al, 2007), and, as expected, were reported as being used in almost all (92%) of respondents’ sales classes at one time or another. However, it appears that role-plays must be supplemented with “working life” experiential exercises to be most effective.…”
Section: Discussionsupporting
confidence: 67%
“…In one form of experiential learning, the use of role-plays, case analyses, simulations, sales presentations, and other activities allows educators to bring the practical nature of sales into the classroom, adding realism to theory (Bobot, 2010). Role-plays are reportedly a traditional mainstay of experiential sales training (Inks & Avila, 2008;Moncrief, 1991;Moncrief & Shipp, 1994;Sojka & Fish, 2008;Taute, Heiser, & McArthur, 2011;Widmier, Loe, & Selden, 2007), becoming particularly effective when students receive constructive feedback and reflect on their performance (Carroll, 2006;Peltier et al, 2005Peltier et al, , 2006.…”
Section: Hypothesis 1amentioning
confidence: 99%
“…Reviews of pedagogical techniques noted the need for integration of sales projects and classroom-based selling experiences when designing sales courses (J. D. Chapman & Avila, 1991;Kimball, 1991). Calls for enhanced course inclusion of relationship development, nonverbal communications, and sales-specific technology and ethics training were discussed (e.g., Anderson et al, 2005;Berman & Sharland, 2002;Taute, Heiser, & McArthur, 2011). Finally, a small group of scholars provided context for the discussion of the current state of sales curricula versus previous sales education eras.…”
Section: Assessmentmentioning
confidence: 99%
“…In other words, we were interested in whether the automatically extracted nonverbal behavior of the applicant would also predict future job performance, especially when the job contains social interactions as a main characteristic, such as sales. Based on previous research showing that the nonverbal behavior of sales people predicts job performance (Leigh & Summers, 2002;Peterson, 2005;Taute, Heiser, & McArthur, 2011;Wood, 2006), we assumed that for sales, the applicant's nonverbal behavior revealed during the job interview might be indicative for future job performance. And indeed, using a door-to-door sales job, we found that the applicant's vocal nonverbal cues such as speaking time, audio back-channeling, and speech fluency all together predicted objectively measured job performance (Frauendorfer, Schmid Mast, Nguyen, & Gatica-Perez, 2013a).…”
Section: Nonverbal Behavior In the Job Interview 29mentioning
confidence: 99%